A critique of the progress of eTourism technology acceptance research: time for a hike?. (10th July 2019) - Pourfakhimi, Shahab; Duncan, Tara; Coetzee, Willem
Abstract : Purpose: The purpose of this study is to evaluate eTourism technology acceptance literature to illustrate current gaps in the field and suggest two alternative perspectives that could be adopted. Design/methodology/approach: A review of academic literature in the field of eTourism technology acceptance was undertaken combining a systematic keyword-based search and snowballing techniques leading to the identification of relevant academic journal articles published since the year 2000. Findings: While the field of eTourism technology acceptance research has grown substantially over the past few decades, this study highlights that the majority of this research seems to have been conducted within a narrow theoretical scope. The study suggests that this has led to contemporary theoretical and philosophical advancements in understanding the psychological, sociological and neuroscientific aspects of consumer behaviour not yet being mirrored in the eTourism technology acceptance research. Research limitations/implications: This study invites researchers to adapt alternative theoretical perspectives to create a more in-depth understanding of aspects of technology acceptance behaviour that have yet to be understood. Two distinct alternative perspectives, NeuroIS and interpretivism, are suggested. Practical implications: This study assists researchers in developing alternative research agendas and diversifying the theoretical foundations of eTourism technology acceptance research. Originality/value: eTourism technology acceptance research risks being left behind if it does not begin to think beyond current theoretical conceptions of consumer behaviour research. This study contributes to the wider literature by highlighting how eTourism literature is falling behind and by suggesting two innovative alternatives that allow eTourism research an exciting way forward. Abstract : 论eTourism技术接受研究的述评：是时候远足? 摘要 研究目的: 本论文旨在审视eTourism技术接受研究文献, 以指出当前文献的不足, 并且提出两个未来可能研究方向。 研究设计/方法/途径: 研究样本为关于eTourism技术接受研究的文献, 文献搜集方法采用系统关键词搜索和雪球搜索技术, 共74篇相关研究文献, 发表年代为2000年至今。 研究结果: eTourism技术接受研究自过去几十年的发展, 其研究成果已经显著增长。本论文强调这方面研究大多数局限在一个狭小理论领域中。本论文建议此方面的研究可以扩展到心理学 社会学 神经科学等消费者行为的领域, 提高eTourism技术接受研究的现代理论和哲学进步, 而这些方面在eTourism技术接受研究领域中, 还未涉足。 研究理论限制/意义: 本论文邀请学者采用其他理论角度来增强技术接受行为的深入理解。两个显著研究方向包括NeuroIS和解释主义。 研究实际意义: 本论文启示学者在eTourism技术接受研究方面的开发新的研究征程, 以及丰富其相关理论基础。 研究原创性/价值: eTourism技术接受研究将被落下, 如果学者不扩展当前关于消费者行为方面的理论基础。本论文拓宽了对eTourism文献的论述, 并且就其如何可能研究落后以及建议两个创新性方向, 使得eTourism研究将有一个崭新前进。 关键词: 技术接受、电子旅游、技术接受模型(TAM)、神经资讯系统(NeuroIS)、 神经科学旅游(Neurotourism)、解释主义